Dynamic Model of Markets of Homogenous Non-Durables - Joachim Kaldasch (British Journal of Economics, Management & Trade, 2015)
A new microeconomic model is presented that aims at a description of the long-term unit sales and price evolution of homogeneous non-durable goods in polypoly markets. It merges the product lifecycle approach with the price dispersion dynamics of homogeneous goods. The model predicts a minimum critical lifetime of non-durables in order to survive. Under the condition that the supply side of the market evolves much faster than the demand side the theory suggests that unsatisfied demands are present in the first stages of the lifecycle. With the growth of production capacities these demands disappear accompanied with a logistic decrease of the mean price of the good. The model is applied to electricity as a non-durable satisfying the model condition. The presented theory allows a deeper understanding of the sales and price dynamics of non-durables.
Keywords: D; P42; L1; 330; non-durables; homogeneous goods; product lifecycle; economic growth; price dispersion; electricity market; Energy market